Repulsion - CARR, JEREMY ([S.l.] : AUTEUR PUBLISHING, 2021)
This Devil's Advocate considers Roman Polanski's Repulsion (1965) within the context of familiar horror tropes and the prevailing qualities of Polanski's broader oeuvre. Drawing on concepts of abjection, the 'monstrous-feminine', and the psychology of horror spectatorship, this text focuses on central themes of isolation, sexuality and setting.
Includes bibliographical references (pages 97-100).
JSTOR
Keywords: Polanski, Roman -- Criticism and interpretation; Repulsion (Motion picture); Polanski, Roman; Individual film directors, film-makers.; Film theory & criticism; Performing Arts -- Film & Video -- History & Criticism; Film studies; London; Polanski; European cinema; British cinema; Criticism, interpretation, etc